Single Center Retrospective Review of Post-laparotomy CT Abdomen and Pelvis Findings and Trends - Steffey, Dylan C.; Chishti, Emad A.; Acevedo, Maximo J.; Acosta, Luis F.; Lee, James T. (Frontiers in Radiology, 2022)
Purpose To identify common findings visualized on CT following damage control laparotomy, including post-surgical changes and additional injuries, and to determine change in frequency of post-laparotomy CT at our institution over time. Methods Single institution, IRB-Exempt, retrospective review of the University of Kentucky trauma registry from 1/2006 to 2/2019 for all trauma patients undergoing exploratory laparotomy initially and subsequently undergoing CT of the abdomen and pelvis within 24 hours. Operative findings from surgical operation notes and findings reported on post-laparotomy CT were recorded, including vascular and solid organ injuries, operative changes, free intraperitoneal fluid/air, and retroperitoneal findings. Next steps in management were also recorded. Results In total 1,047 patients underwent exploratory laparotomy initially at our institution between 1/2006-2/2019. Of those, only 96 had a diagnostic CT of the abdomen and pelvis within 24 h after initial surgery, first occurring in 2010. Among these 96, there were 71 blunt and 25 penetrating injuries. Most common injuries recognized during exploratory laparotomy were bowel/mesentery (55), spleen (34), and liver (26). Regarding CT findings, all patients (96/96, 100%) had residual pneumoperitoneum, 84/96 (87.5%) had residual hemoperitoneum, 36/96 (37.5%) noted post-surgical changes or additional injuries to the spleen, 36/96 (37.5%) to the bowel/mesentery, and 32/96 (33.3%) to the liver, and 34/96 (35.4%) were noted to have pelvic fractures. After CT, 31/96 (32.3%) went back to the OR for relook laparotomy and additional surgical intervention and 7/96 (7.3%) went to IR for embolization. Most common procedures during relaparotomy involved the bowel (8) and solid organs (6). Conclusions CT examination within 24 h post damage control laparotomy was exceedingly rare at our institution prior to 2012 but has steadily increased. Frequency now averages 20.5% yearly. Damage control laparotomy is an uncommon clinical scenario; however, knowledge of frequent injuries and common post-operative changes will aid in radiologist detection of additional injuries helping shape next step management and provide adequate therapy.